2000
DOI: 10.1182/blood.v96.4.1574.h8001574_1574_1581
|View full text |Cite
|
Sign up to set email alerts
|

Blood group A and B antigens are strongly expressed on platelets of some individuals

Abstract: It is widely thought that expression of ABH antigens on platelets is insufficient to materially affect the survival of ABH-incompatible platelets in transfusion recipients, but anecdotal reports of poor survival of A and B mismatched platelets suggest that this is not always the case. The A and B antigen expression on platelets of 100 group A1 and group B blood donors was measured, and 7% and 4%, respectively, had platelets whose A and B antigen levels consistently exceeded the mean plus 2 SD. On the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 34 publications
4
39
2
Order By: Relevance
“…A limitation of some older studies is that nonidentical transfusions were not categorized into minor-(plasma-incompatible) and major-(PLT-incompatible) mismatched transfusions, bearing the risk that significant differences in transfusion efficacy between ABO-identical and major-mismatched PLTs could have been missed. 17 In accordance with earlier reports, 5,6 we observed a dramatic diversity in the percentages of PLTs expressing A antigen among A1 donors (median, 40%; range, 3%-80%). High A antigen expression may be the main pathophysiologic mechanism explaining the rapid clearance of these PLTs from circulation after transfusion into group O or B recipients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A limitation of some older studies is that nonidentical transfusions were not categorized into minor-(plasma-incompatible) and major-(PLT-incompatible) mismatched transfusions, bearing the risk that significant differences in transfusion efficacy between ABO-identical and major-mismatched PLTs could have been missed. 17 In accordance with earlier reports, 5,6 we observed a dramatic diversity in the percentages of PLTs expressing A antigen among A1 donors (median, 40%; range, 3%-80%). High A antigen expression may be the main pathophysiologic mechanism explaining the rapid clearance of these PLTs from circulation after transfusion into group O or B recipients.…”
Section: Discussionsupporting
confidence: 91%
“…1,2 PLTs express ABH blood group antigens on their surface, some of them at very high levels. [3][4][5][6] After ABO major-mismatched transfusions, transfused PLTs may be directly affected by the recipient's isohemagglutinins, the naturally occurring ABO antibodies, leading to premature destruction of the transfused incompatible PLTs. Furthermore, transfusion of ABO minor-incompatible PLTs stored in plasma containing anti-A and/or anti-B antibodies can lead to a hemolytic transfusion reaction in the recipient.…”
mentioning
confidence: 99%
“…2,13,14,16,26,3638 It is reported that patients after major ABO mismatched trans plantation are at increased risk of immediate hemolytic reaction due to preformed recipient IA binding to donor RBC present in the stem As donor platelets might be targets for above described anti donor IA due to surface expression of A and B blood group antigens, this could explain the inhibition of platelet regeneration and the sub sequent increased need for platelet transfusions. 26,42,43 By performing subgroup analysis of the individuals with major ABO mismatch, we found that significantly more RBC and platelet transfusions were required, and platelet recovery was significantly delayed only in the group with major 0 mismatch. Recently, it has been reported that delayed RBC engraftment and PRCA occur mainly in major 0 mismatched transplantation.…”
Section: Discussionmentioning
confidence: 93%
“…Maternal serum was tested against paternal PLTs and a typed panel of normal PLTs for PLT-reactive and GP-specific antibodies as previously described 17 using flow cytometry and/or modified capture enzyme-linked immunosorbent assay (MACE). 8,18,19 Genotyping for antigens HPA-1 through -6, -9, and -15 was carried out using in-house allelic discrimination assays described previously. 20 Diagnosis of NAIT was considered to be confirmed when a maternal antibody was identified that recognized an HPA present in the father or, in rare cases, was specific for GPIV (CD36); other cases were considered to be "unresolved."…”
Section: Patientsmentioning
confidence: 99%